An Empirical Investigation of Oil-Macro-Financial Linkages in Saudi Arabia - Miyajima, Ken. (Washington, D.C. : International Monetary Fund, 2016)
Oil-macro-financial linkages in Saudi Arabia are analyzed by applying panel econometric frameworks (multivariate and vector autoregression) to maceoeconomic and bank-level balance sheet data for 9 banks spanning 1999-2014. Lower growth of oil prices and non-oil private sector output leads to slower credit and deposit growth and higher nonperforming loan ratios, with feedback loops within bank balance sheets which in turn dampens economic activity. U.S. interest rates are not found to be a key determinant.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet